Real-world safety of ixekizumab: a disproportionality analysis using the FDA adverse event reporting system and the VigiAccess databases - Zhao, Kaidi; Tan, Xuanfeng; Qin, Miao; Li, Qinxiao; Meng, Qinqin; Liu, Ying; Li, Jing; Liu, Jiashu (Frontiers in Medicine, 2025)
IntroductionIxekizumab is a biologic agent primarily indicated for the treatment of moderate to-severe plaque psoriasis. This study aimed to evaluate the post-marketing safety profile of ixekizumab by analyzing adverse event (AE) reports retrieved from the Food and Drug Administration Adverse Event Reporting System (FAERS) database and VigiAccess databases.MethodsFour disproportionality analysis methods were employed in this study to detect positive signals associated with ixekizumab, including Reporting Odds Ratio (ROR), Proportional Reporting Ratio (PRR), Bayesian Confidence Propagation Neural Network (BCPNN), and Multi-item Gamma Poisson Shrinker (MGPS). Sensitivity analyses were conducted to ensure the robustness of the findings. Additionally, the time to onset of AEs was further analyzed.ResultsIn the FAERS databases and VigiAccess databases, 72,847 AE reports in total. Commonly reported AEs included injection site reactions, hypersensitivity reactions, fungal infections, upper respiratory tract infections, and inflammatory bowel disease. In addition, several unexpected AEs were identified, such as cellulitis, ear infection, bronchitis, herpes zoster, tooth infection, diverticulitis, kidney infection, and gastroenteritis viral. Sensitivity analysis further confirmed the robustness of these findings. Notably, 41.1% of the AEs occurred within the first month after treatment initiation.DiscussionThis study confirmed several known AEs and identified some unexpected AEs, providing preliminary safety insights to guide clinicians in the safe use of ixekizumab in clinical practice. It is important to note that findings from spontaneous adverse event reporting systems are hypothesis-generating and may be limited by underreporting, variable reporting quality, and confounding factors.